2009
DOI: 10.1007/s11207-009-9396-8
|View full text |Cite
|
Sign up to set email alerts
|

Type II bursts in Meter and Decameter – Hectometer Wavelength Ranges and Their Relation to Flares and CMEs

Abstract: Statistical analysis of the relationship between type II radio bursts appearing in the metric (m) and decameter-to-hectometer (DH) wavelength ranges is presented. The associated X-ray flares and coronal mass ejections (CMEs) are also reported. The sample is divided into two classes using the frequency-drift plots: Class I, representing those events where DH-type-II bursts are not continuation of m-type-II bursts and Class II, where the DH-type-II bursts are extensions of m-type-II bursts. Our study consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…The flare rise time (time interval between flare start and flare peak) is the most important parameter in analyzing the relationship between flares, CMEs and type II radio bursts (Shanmugaraju et al 2003;Subramanian et al 2003;Zhang et al 2004;Prakash et al 2009. The distribution of rise times (a), duration (b), and peak flux (c) of all 45 events (top) SEPassociated flares (middle) and non-SEP-associated flare (bottom) events is shown in Figure 6.…”
Section: Characteristics Of Sep-associated and Non-sep-associated Flaresmentioning
confidence: 99%
See 1 more Smart Citation
“…The flare rise time (time interval between flare start and flare peak) is the most important parameter in analyzing the relationship between flares, CMEs and type II radio bursts (Shanmugaraju et al 2003;Subramanian et al 2003;Zhang et al 2004;Prakash et al 2009. The distribution of rise times (a), duration (b), and peak flux (c) of all 45 events (top) SEPassociated flares (middle) and non-SEP-associated flare (bottom) events is shown in Figure 6.…”
Section: Characteristics Of Sep-associated and Non-sep-associated Flaresmentioning
confidence: 99%
“…In addition, recent studies have pointed out that CMEs associated with longer and stronger solar flares can generate type II radio bursts in different radio wavelength domains. It could be an early indicator to predict the space weather conditions (Micha lek et al 2003;Yashiro et al 2004;Gopalswamy et al 2005;Prakash et al 2009Prakash et al , 2010Prakash et al , 2014Suresh & Shanmugaraju 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…The flare rise-time (interval Fig. 3 Distribution of: (a) flare rise-times; (b) flare decay-times, for DH CMEs following and preceding the associated flares (left and right respectively) from flare start to flare peak) is the most important parameter in analyzing the relationship between flares and CMEs (Shanmugaraju et al 2003;Subramanian et al 2003;Zhang et al 2004;Prakash et al 2009). As seen from Fig.…”
Section: The Flare Rise-time and Decay-timementioning
confidence: 99%
“…Flare rise time (the interval from the flare start to flare peak) is the most important parameter in analyzing the relationship between flares and type-II bursts. Shanmugaraju et al (2003) and Prakash et al (2009) studied the relation between the flare-CMEs-metric type-II radio bursts. They found that the coronal shock is formed between the start and peak of the X-ray flare.…”
Section: Properties Of Flares and Cmes Of Group I Ii And Iii Eventsmentioning
confidence: 99%